Cryogenic X-ray crystallographic studies of biomacromolecules at Turkish Light Source Turkish DeLight - Atalay, Necati; Akcan, Enver Kamil; Gul, Mehmet; Ayan, Esra; Destan, Ebru; Ertem, Fatma Betuel; Tokay, Nurettin; Cakilkaya, Baris; Nergiz, Zelis; Karakadioglu, Gozde; Kepceoglu, Abdullah; Yapici, Ilkin; et al. (Tubitak Scientific & Technological Research Council Turkey, 2023)
X-ray crystallography is a robust and powerful structural biology technique that provides high-resolution atomic structures of biomacromolecules. Scientists use this technique to unravel mechanistic and structural details of biological macromolecules (e.g., proteins, nucleic acids, protein complexes, protein-nucleic acid complexes, or large biological compartments). Since its inception, single-crystal cryocrystallography has never been performed in Turkiye due to the lack of a single-crystal X-ray diffractometer. The X-ray diffraction facility recently established at the University of Health Sciences, Istanbul, Turkiye will enable Turkish and international researchers to easily perform high-resolution structural analysis of biomacromolecules from single crystals. Here, we describe the technical and practical outlook of a state-of-the-art home-source X-ray, using lysozyme as a model protein. The methods and practice described in this article can be applied to any biological sample for structural studies. Therefore, this article will be a valuable practical guide from sample preparation to data analysis.
Keywords: X-ray crystallography; light source; structural biology; atomic resolution; drug repurposing; drug development; structural dynamics; DIFFRACTION; SCATTERING; DETECTORS; BEAMLINE; Life Sciences & Biomedicine - Other Topics